ECONOMIC VIEWS OF THE TURKESTAN JADIDS (Scientific journal of the Fergana State University, 2023)
This article analyzes the economic views of the Turkestan Jadids. The study of the content, essence and conceptual significance of the economic ideas of the Jadids, such as the concept of national awakening and economic growth, training young people in modern professions for the economic development of society, the creation of handicraft schools The authors explore the theoretical and practical aspects of the ideas put forward by the Jadids regarding the secular education of young people in developed countries, their education at leading universities, and professional development. The futurological aspects of the views of enlightened Jadids on respect for the Motherland, the effective use of these resources for national development, and the factors of the country's economic development are studied.